2015
DOI: 10.1074/jbc.m115.652123
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Engineering of Phytochelatin-based Heavy Metal Tolerance

Abstract: Background: Plants synthesize phytochelatin peptides for protection against heavy metals. Results: Metabolic engineering in yeast and plants using a phytochelatin synthase variant leads to improved cadmium tolerance. Conclusion: Enhanced cadmium tolerance results from a balance between phytochelatin synthesis and redox state. Significance: Our results emphasize the importance of metabolic context for pathway engineering and broaden the range of tools for environmental remediation.Metabolic engineering approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…This enzyme catalyzes the synthesis of phytochelatin from glutathione at basal levels and in the presence of metal ions like Cd 2+ , Zn 2+ , Cu 2+ , and Fe 3+ . It has been recently used to engineer heavy metal tolerance in plants (Cahoon et al, 2015 ) and to engineer cadmium biosensers in yeast (Matsuura et al, 2013 ), and its over-expression in tobacco has been shown to enhance arsenic and cadmium detoxification (Zanella et al, 2015 ). However, the ubiquitous nature and constitutive expression of phytochelatin synthases suggest a rather more generalized function besides metal detoxification, as PCS1 was later shown to be involved in non-host resistance (Clay et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…This enzyme catalyzes the synthesis of phytochelatin from glutathione at basal levels and in the presence of metal ions like Cd 2+ , Zn 2+ , Cu 2+ , and Fe 3+ . It has been recently used to engineer heavy metal tolerance in plants (Cahoon et al, 2015 ) and to engineer cadmium biosensers in yeast (Matsuura et al, 2013 ), and its over-expression in tobacco has been shown to enhance arsenic and cadmium detoxification (Zanella et al, 2015 ). However, the ubiquitous nature and constitutive expression of phytochelatin synthases suggest a rather more generalized function besides metal detoxification, as PCS1 was later shown to be involved in non-host resistance (Clay et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to knockout engineering, fine-tuning enzymatic activity can also tailor plant responses to toxic metals. Directed evolution of phytochelatin synthase (PCS), an enzyme that synthesizes heavy metal-binding peptides, revealed an unexpected way of improving heavy metal tolerance through the attenuation of enzymatic activity (43). A catalytically inferior PCS resulted in phenotypic superiority because it maintained cellular redox homeostasis while synthesizing peptides for detoxification of cadmium (43).…”
Section: Environmental Engineering For Remediationmentioning
confidence: 99%
“…No form of phytochelatin was detected; however, phytochelatin synthase activity is only detectable in the presence of heavy metal stress (Cahoon et al . ).…”
Section: Resultsmentioning
confidence: 97%